Analysis Of Company Performance Effect On Share Price Study On Construction Sub Sector Companies Registered In Bursa Efek Indonesia (BEI) - Dhea Zatira; Ari Nuratriningrum; Andy Andy; Sutandi Sutandi (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This study aims to examine the effect of Company Performance on Share Prices in the Sub-Construction Sector Companies listed on the Indonesia Stock Exchange in the 2015-2018 Period. Company Performance Measurement uses the ratio of Earning Per Share (EPS), Price to Book Value (PBV), Return to Assets Ratio (ROA), Debt to Equity Ratio (DER) and Gross Profit Margin. The data analysis technique used in this study is a panel data regression model using E-Views software. The test results prove that Earning Per Share has an influence on stock prices. Price to Book Value affects the stock price. Return On Assets has no effect on stock prices. Debt to Equity Ratio has no effect on the stock price. Gross Profit Margin has no effect on stock prices. And together Earnings Per Share, Price To Book Value, Return On Assets, Debt to Equity Ratio and Gross Profit Margin affect the Stock Price